Pattern and Processes in Agroforestry Systems of the Western Himalaya - Khosla, P.K.; Toky, O.P. (Indian Journal of Agroforestry, 2020)
Traditional agroforestry systems having several MPTs along the bund of agricultural lands or scattered trees on the pasturelands were developed throughout the western Himalaya depending upon the needs, economics and environmental status of the land. Species diversity, production potential and soil fertility, and consequently, the sustainability of the agroforestry systems varies enormously. High rate of net primary productivity has been reported in agrihortisilvicultural systems (26 t ha-1 yr-1) or agrihorticultural systems (23 t ha-1 yr-1), and the species number in these systems is as high as 15 tree species. The values of production are comparable to highly productive forests or plantations of the tropical and subtropical regions. Maximum stock of nutrients in the standing biomass is present in fruit-based agroforestry systems, and considerable quantity of nutrients is recycled through debris of crops and weeds and tree leaf litter. Nevertheless, in these systems there is heavy export of nutrients through harvesting of fruits, and potassium is depleted in the maximum quantity followed by nitrogen; hence, making the nutrient cycling "open". To maintain the sustainability of such systems, the lost nutrients need to be replenished annually through manure and/or fertilizers. The strategy of agroforestry in the western Himalaya should include development of common lands by culturing fuel-fodder-wild fruit trees on the concept of small watersheds. Timber wood lots of MPTs for supporting cottage industries may help to improve the socio-economic status of the rural people. The objective of conservation of natural resources (soil, water, biota) should also be considered.